Sustaining harbor operation and maintenance in Maldives. - Heriawan, Andri (Metro Manila, Philippines Asian Development Bank, 2018)
This brief explores investments in harbor infrastructure, operation, and maintenance in Maldives.In 2016, the Government of Maldives received a grant amounting to 9.69 million from ADB to construct a new passenger and cargo harbor as an expansion of the existing multipurpose harbor on Kulhudhuffushi Island. For the investment in the harbor infrastructure to be effective and sustainable, ADB provided technical assistance of 0.5 million to support the government to (i) enhance the institutional capacity of the operator in harbor operation, maintenance, safety, and financial management; and (ii) help promote income-generating livelihood opportunities for local communities in the northern region. The project improved interisland connectivity in the northern region by increasing (i) harbor passenger and cargo capacity in Kulhudhuffushi and (ii) institutional capacity in harbor operation, maintenance, safety, and financial management. This document summarizes the challenges and recommended mitigation actions for the Government of Maldives in sustaining harbor operation and maintenance.
Keywords: Harbors -- Maldives -- Management; Harbors -- Maintenance and repair -- Finance; Electronic books